SURVEY ON INSECT PESTS, BIOEFFICACY OF CERTAIN INSECTICIDE MOLECULES AGANIST THRIPS ON CAPSICUM (Capsicum annuum L. var. grossum Sendt.) UNDER POLY HOUSE CONDITIONS - BHARATI N. BHAT, V. L. PATHIPATI, T. V. K. SINGH, V. SHASHIBHUSHAN, R. V. S. K. REDDY and (The Journal of Research, PJTSAU, 2019)
Fixed plot survey in and around Hyderabad, Telanganarevealed that thrips, Scirtothripsdorsalis Hood, mites, Polyphagotarsonemuslatus Banks cut worm, Agrotisipsilon (Hufn.), blossom midge, Asphondyliacapsici Barnes and fruit borer, Spodopteralitura Fab incidence was recorded under open field conditions where as aphids and whiteflies were recorded in addition to above insect pests under poly house conditions. Bio-efficacy of insecticides against thripsof capsicum, under poly house conditions in the 2013-14 and 2014-15, revealed that mean thrips population in pre count ranged from 1.07 to 4.34 and post count population was lower with spinosad(0.06 thrips/leaf) followed by diafenthiuron (0.50 thrips/leaf) and thiomethoxam (1.30 thrips/leaf) which were significantly superior over untreated check (5.6 thrips/leaf) and at par with each other. The mean Leaf Curl Index (LCI) of two years revealed that, LCI at one DBS (1.25) was significantly reduced to 0.51 in spinosad treated plants followed by diafenthiuron (1.69 to 0.90) and thiomethoxam (1.82 to 1.16). Whereas, LCI was significantly increased from one DBS to 10 DAS in chlorantraniliprole (2.41 to 2.51),flubendiamide (2.43 to 2.55), spiromesifen (2.51 to 2.64) and triazophos (2.53 to 2.72) and untreated check (2.71 to 2.96) The results obtained from the both years of poly house experiment clearly showed that, spinosadwas significantly superior over rest of the treatments and showed lowest mean no. of thrips per leaf (0.06) and mean reduction of thrips population (98.05 %). Next best treatment was diafenthiuron in reducing mean thrips population (0.50) and increased mean per cent reduction of population (72.98 %) followed by thiomethoxam whichshowed significant superiority in reducing mean thrips population (1.30) and moderate mean per cent reduction of thrips population (72.98).